Societal sentience: constructions of the public in animal research policy and practice - Hobson-West, Pru; Davies, Ashley (Sage, 2017)
The use of non-human animals as models in research and drug testing is a key route through which contemporary scientific knowledge is certified. Given ethical concerns, regulation of animal research promotes the use of less ‘sentient’ animals. This paper draws on a documentary analysis of legal documents, and qualitative interviews with Named Veterinary Surgeons and others at a commercial laboratory in the UK. Its key claim is that the concept of animal sentience is entangled with a particular imaginary of how the general public or wider society views animals. We call this imaginary societal sentience. Against a backdrop of increasing ethnographic work on care encounters in the laboratory, this concept helps to stress the wider context within which such encounters take place. We conclude that societal sentience has potential purchase beyond the animal research field, in helping to highlight the affective dimension of public imaginaries (Welsh and Wynne 2013), and their ethical consequences. Researching and critiquing societal sentience, we argue, may ultimately have more impact on the fate of humans and non-humans in the laboratory, than focusing wholly on ethics as situated practice.